2024
DOI: 10.3847/1538-4357/ad167e
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Red Galaxies at z = 5–9 with MIRI and NIRSpec: Dusty Galaxies or Obscured Active Galactic Nuclei?

Guillermo Barro,
Pablo G. Pérez-González,
Dale D. Kocevski
et al.

Abstract: We study a new population of extremely red objects (EROs) recently discovered by the James Webb Space Telescope (JWST) based on their NIRCam colors F277W − F444W > 1.5 mag. We find 37 EROs in the Cosmic Evolution Early Release Science Survey (CEERS) field with F444W < 28 mag and photometric redshifts between 5 < z < 7, with median z = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 126 publications
6
33
0
Order By: Relevance
“…We exclude the two galaxies that Leung et al (2023) found had red colors in the longwavelength bands. As discussed in Leung et al (2023), this may indicate that these sources have an AGN component contributing to their emission, similar to other sources identified at brighter magnitudes and lower redshifts (e.g., Kocevski et al 2023;Labbe et al 2023;Matthee et al 2023;Barro et al 2024).…”
Section: Galaxy Samplesupporting
confidence: 76%
“…We exclude the two galaxies that Leung et al (2023) found had red colors in the longwavelength bands. As discussed in Leung et al (2023), this may indicate that these sources have an AGN component contributing to their emission, similar to other sources identified at brighter magnitudes and lower redshifts (e.g., Kocevski et al 2023;Labbe et al 2023;Matthee et al 2023;Barro et al 2024).…”
Section: Galaxy Samplesupporting
confidence: 76%
“…The BH masses for those JWST-detected faint AGNs are M • ∼ 10 6−8 M e , which is 1-2 orders of magnitude lower than those of previously known quasars at z > 4. Intriguingly, some of the sources have extremely red colors in the rest-frame optical bands, while the rest-frame UV color seems fairly consistent with those of known Lyman-break galaxies at similar redshifts (e.g., Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Greene et al 2024;Matthee et al 2024). The so-called "little red dot" sources are interpreted to be in a transition stage from a dust-obscured starburst to an unobscured luminous quasar due to the expelling of gas and dust (Fujimoto et al 2022).…”
Section: Introductionsupporting
confidence: 59%
“…2. An intriguing subset consists of the dust-reddened AGNs (referred to as "little red dots"), characterized by moderate obscuration in the SED and compact morphology (Harikane et al 2023;Kocevski et al 2023;Labbe et al 2023;Barro et al 2024;Matthee et al 2024). This class of AGNs shows a distinctive spectral shape, which can be attributed to a dust-reddened AGN continuum coupled with excess emission in the rest-frame UV produced either by the unobscured stellar continuum of the host galaxy or scattered light from the buried AGN (e.g., Zakamska et al 2005;Polletta et al 2006;Noboriguchi et al 2023).…”
Section: Populationsmentioning
confidence: 99%
“…One source, CEERS-EGS-BD-5, has an EAZY galaxy fit with χ 2 = 18.31, but we included this source in our final sample as the EAZY fit is not consistent with the nondetections in the ACS F606W and F814W filters. We rejected those sources with red LW slopes similar to those described in Endsley et al (2023), Furtak et al (2023, Barro et al (2024), Hainline et al (2023), , and Matthee et al (2023), as these have colors inconsistent with brown dwarf models.…”
Section: Selecting Brown Dwarf Candidatesmentioning
confidence: 96%
“…Multiple authors have looked at similar samples of extremely red sources in extragalactic data sets (e.g., Franco et al 2023;Pérez-González et al 2023, Barro et al 2024, among others), and we have outlined color selection criteria here which may be used to find the brown dwarfs among those samples.…”
Section: Comparing To High-redshift Galaxy Colorsmentioning
confidence: 99%